2017
DOI: 10.17576/mjas-2017-2101-06
|View full text |Cite
|
Sign up to set email alerts
|

MOLLUSCICIDAL ACTIVITY OF Entada rheedii STEM BARK METHANOLIC EXTRACT AGAINST PADDY PEST Pomacea canaliculata (GOLDEN APPLE SNAIL)

Abstract: The study was conducted to evaluate the molluscicidal activity of E. rheedii methanol bark extract against P. canaliculata and to screen for phytochemical compounds of E. rheedii bark extracts. The golden apple snails with size range of 20 -40 mm were treated with four different concentrations of E. rheedii (1000, 5000, 10000 and 20000 ppm) and paddy-field water mix with 50% methanol serving as the control treatment. The molluscicidal effects of the extract were evaluated after 24, 48 and 72 hours. The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…A total of 200 adult snails (18 -25 mm) were collected from the paddy field in Pekan, Pahang, Malaysia. They were acclimatized to the laboratory environment (25℃) for three days and fed with papaya leaves [15,16], after which snails were randomly selected for the molluscicidal study.…”
Section: Sampling Of P Canaliculatamentioning
confidence: 99%
“…A total of 200 adult snails (18 -25 mm) were collected from the paddy field in Pekan, Pahang, Malaysia. They were acclimatized to the laboratory environment (25℃) for three days and fed with papaya leaves [15,16], after which snails were randomly selected for the molluscicidal study.…”
Section: Sampling Of P Canaliculatamentioning
confidence: 99%
“…Golden Apple Snails (GAS) or commonly known as Siput Gondang Emas is a large freshwater snail that is native to tropical and subtropical South America (Liu et al 2018). In 1987, GAS (Mollusca: Ampullariidae: Pomacea canaliculata) was introduced in Malaysia as a food item and aquarium pet, but now it is one of the most serious pests that caused extreme damage to paddy fields (Nur Suraya, Noorshilawati & Rosminah 2017). Yahaya et al (2017) reported that GAS is highly invasive and caused a drastic reduction in the production of rice in ASEAN countries, especially in Malaysia causing losses amounting to RM82 million in 2010.…”
Section: Introductionmentioning
confidence: 99%